Potentiometric determination of stability constants and thermodynamic data for ternary Cd(II) complexes with 2-aminomethyl benzimidazole (AMBI) and other bioactive ligands - Aljahdali, Mutlaq Shedeed (European Journal of Chemistry, 2013)
The complexing properties of 2-(aminomethyl)-benzimidazole with cadmium(II) were investigated pH-metrically at 25 oC and at ionic strength of 0.1 mol.dm-3 (NaNO3). Ternary complex formation equilibria of cadmium(II) complexes involving (AMBI) and some bio-relevant ligands (L = amino acid and peptides) have been investigated. Ternary complexes of amino acids and peptides are formed by a simultaneous mechanism. Amino acids form the complex Cd(AMBI)L, whereas amides form two complex species Cd(AMBI)L and Cd(AMBI)(LH-1). The stability of ternary complexes was quantitatively compared with their corresponding binary complexes in terms of the parameters ΔLog K, Log βStat and Log X. The effect of the side chains of amino acid ligands (ΔR) on complex formation was discussed. The values of ΔLog K indicate that the ternary complexes containing aromatic amino acids are significantly more stable than the complexes containing alkyl- and hydroxyalkyl-substituted amino acids. This may be taken as evidence for a stacking interaction between the aromatic moiety of AMBI and the aromatic side chains of the bioactive ligands. The concentration distributions of various species formed in solution were also evaluated as a function of pH. The thermodynamic parameters ΔHo, ΔGo and ΔSo calculated from the temperature dependence of the equilibrium constants were investigated for the interaction of Cd(II)-AMBI with glycine as a representative example of amino acids.